Use of biomedical photonics in gynecological surgery: a uterine transplantation model - Saso, Srdjan (Future Sci OA, 2018)
AIM: Uterine transplantation (UTx) has been proposed as a treatment for permanent absolute uterine factor infertility. The study aims were to compare pulse oximetry and multispectral imaging (MSI), for intraoperative tracking of uterine oxygen saturation in animal UTx models (rabbit and sheep). RESULTS/METHODOLOGY: Imaging results confirmed the re-establishment of adequate perfusion in the transplanted organ after surgery. Comparison of oxygen saturation values between the pre-UTx donor and post-UTx recipient, and pre-UTx and post-UTx recipient reveals a statistically significant decrease in saturation levels post-UTx. CONCLUSION: The use of MSI is the first case in gynecology and has demonstrated promise of possible future human use. MSI technique has advantages over pulse oximetry – it provides spatial information in a real-time, noncontact manner.